Oxygen-doped sulfide solid electrolyte and preparation method thereof

By doping oxygen into the sulfide solid electrolyte in the lithium-ion battery, the problem of small electrochemical stability window and interface reaction is solved, and the high voltage compatibility and long life of the battery are achieved.

CN119742427APending Publication Date: 2025-04-01CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411778314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The sulfur-silver germanium ore-type sulfide solid electrolyte in existing lithium-ion batteries limits its matching with high-voltage positive electrode material due to the small electrochemical stability window, and is prone to side reactions with the solid-solid interface of the positive electrode material, resulting in attenuation of the battery charge and discharge capacity and affecting service life.

Method used

By doping an appropriate amount of oxygen into the sulfide solid electrolyte, the chemical stability of the electrolyte is improved, the electrochemical stability window is broadened, the interface reaction with the high-voltage positive electrode material is suppressed, and a self-passivated interface SEI layer is formed at the lithium metal interface to improve compatibility with lithium metal.

Benefits of technology

The electrochemical stability window of the electrolyte is achieved with a wider window, which improves compatibility with high-voltage positive electrode materials, suppresses interface reactions, extends the service life of the battery, and improves the charge and discharge capacity and first-cooling efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172098400000131
    Figure BDA0005172098400000131
  • Figure BDA0005172098400000141
    Figure BDA0005172098400000141
  • Figure HDA0005172098410000011
    Figure HDA0005172098410000011
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to an oxygen-doped sulfide solid electrolyte and a preparation method thereof.The chemical general formula of the solid electrolyte is Li < 7-x + 2y + 2zPS < 6-x + y + zMxO4y, M is a halogen element, 0 < = x < = 2, 0 < = y < = 0.02, and 0.1 < = z < = 0.5, by doping a proper amount of oxygen in the solid electrolyte, the stability of the electrolyte is improved, and the service life of the electrolyte is prolonged. According to the preparation method, the electrochemical stability window of the electrolyte is relatively wide, so that the electrolyte can be matched with a high-voltage positive electrode material, the interface reaction between the electrolyte and a high-voltage positive electrode is effectively inhibited, the interface stability between the electrolyte and the positive electrode material is improved, and the first-effect performance and the charge-discharge capacity of the battery are further improved; and the room-temperature ionic conductivity of the sulfide solid electrolyte and the air stability at a low dew point are also improved through proper oxygen doping, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an oxygen-doped sulfide solid electrolyte and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density and long life, so they are widely used as power sources for home appliances such as cameras, portable electronic devices such as notebook computers and mobile phones, power tools and other electric tools, and recently they are also used in large-sized batteries installed in electric vehicles (EV) or hybrid electric vehicles (HEV). However, the current traditional lithium-ion batteries still focus on liquid electrolyte batteries, which use flammable, corrosive and thermally unstable organic solvents as electrolytes, and still have great safety risks in terms of electrochemical stability and thermal stability, and cannot meet the market demand for large-sized batteries.

[0003] The solid electrolyte in all-solid-state batteries is the core material in all-solid-state batteries. Therefore, developing a solid electrolyte with high comprehensive performance such as a wide electrochemical window, high room temperature ionic conductivity, excellent chemical stability and low cost is an important prerequisite for realizing the industrialization of all-solid-state lithium batteries.

[0004] Argentothioate-type sulfide solid electrolytes have the advantages of high ionic conductivity, wide electrochemical stability window, simple synthesis process and low preparation cost. They are currently an important type of sulfide solid electrolytes. However, due to their small electrochemical stability window, they are limited in matching with high-voltage positive electrode materials. In addition, they are prone to continuous side reactions at the solid-solid interface with the positive electrode material, which in turn leads to the attenuation of the battery's charge and discharge capacity and affects the service life of the all-solid-state battery. Summary of the invention

[0005] In view of the above problems of the prior art, the present application provides an oxygen-doped sulfide solid electrolyte and a preparation method thereof, which makes the electrochemical stability window of the solid electrolyte wider, avoids the continuous occurrence of side reactions between the solid-solid interface of the solid electrolyte and the positive electrode material, improves the stability of the electrolyte itself, and thus increases the charge and discharge capacity of the battery and the service life of the battery. The specific technical solution is as follows:

[0006] On the one hand, the present application provides an oxygen-doped sulfide solid electrolyte, the chemical formula of the solid electrolyte is Li 7-x+2y+2z PS 6-x+y+z M x O 4y , wherein M is a halogen element, 0≤x≤2, 0≤y≤0.02, 0.1≤z≤0.5.

[0007] In a possible implementation, 0≤x≤1.9, 0.0009≤y≤0.015, 0.20≤z≤0.45.

[0008] In a possible implementation, 0≤x≤1.7, 0.0018≤y≤0.0144, 0.22≤z≤0.44.

[0009] In a possible implementation manner, the components of the solid electrolyte include oxygen-doped materials, and the oxygen-doped materials are lithium-containing oxides and / or oxygen-containing lithium salts.

[0010] On the other hand, the present application provides a method for preparing the electrolyte as in the above embodiment, comprising:

[0011] S1: providing oxygen-doped powder, lithium source, phosphorus source and halide;

[0012] S2: mixing the oxygen-doped powder, the lithium source, the phosphorus source and the halide to obtain a precursor material;

[0013] S3: calcining the precursor material in an oxygen-free environment to obtain the oxygen-doped sulfide solid electrolyte.

[0014] In a possible implementation manner, the mass ratio between the oxygen-doped material and the lithium salt is (0.01-0.1):1.

[0015] In a possible implementation manner, the method satisfies at least one of the following characteristics:

[0016] The size range of the zirconia balls during the grinding process in step S12 is φ1-φ10;

[0017] The ball-to-material ratio in the grinding process in step S12 is (10-30):1;

[0018] The ball milling speed in the grinding process in step S12 is 50 rpm-250 rpm;

[0019] The ball milling time in the grinding process in step S12 is 0.5-3h;

[0020] The grinding process in step S12 is performed in an oxygen-free environment.

[0021] In a possible implementation manner, the method satisfies at least one of the following characteristics:

[0022] The heating rate during the calcination process in step S3 is 1-5°C / min;

[0023] The calcination temperature in the calcination process in step S3 is 400-550°C;

[0024] The calcination time in the calcination process in step S3 is 6-20 hours.

[0025] In a possible implementation manner, the oxygen-doped material is a lithium-containing oxide and / or an oxygen-containing lithium salt.

[0026] Based on the above technical solution, this application has the following beneficial effects:

[0027] The oxygen-doped sulfide solid electrolyte in the present application has a chemical formula of Li 7-x+2y+ 2z PS 6-x+y+z M x O 4y , wherein M is a halogen element, 0≤x≤2, 0≤y≤0.02, 0.1≤z≤0.5, and by doping the solid electrolyte with an appropriate amount of oxygen content, the chemical stability of the electrolyte itself is improved, and its room temperature ionic conductivity and air stability at low dew points are improved, so that the electrochemical stability window of the electrolyte is wider, so that it can match the high-voltage positive electrode material, and effectively inhibit the interface reaction between it and the high-voltage positive electrode material, improve the interface stability between the electrolyte and the positive electrode material, greatly improve the charge and discharge capacity of the all-solid-state battery, the first coulomb efficiency is increased to more than 81%, and the service life of the all-solid-state battery is extended. At the same time, an appropriate amount of oxygen doping can also help inhibit the growth of lithium dendrites, mainly because the solid electrolyte doped with oxygen can form a self-passivating interface SEI layer at the lithium metal interface, thereby improving its compatibility with lithium metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 This is the XRD spectrum of the oxygen-doped sulfide solid electrolyte obtained in Example 12.

[0030] Figure 2 The graphs are the charge and discharge characteristics of principle cells made with the oxygen-doped sulfide solids of Example 12 (red line) and Comparative Example 1 (blue line) and subjected to battery testing. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0032] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0033] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0034] The following describes the oxygen-doped sulfide solid electrolyte provided in the embodiments of the present application. The chemical formula of the solid electrolyte is Li 7-x+2y+2z PS 6-x+y+z M x O 4y , where M is a halogen element, 0≤x≤2, 0≤y≤0.02, 0.1≤z≤0.5. By doping the solid electrolyte with an appropriate amount of oxygen, oxygen can partially replace sulfur, reducing the possibility of oxygen entering the sulfide electrolyte from the positive electrode, effectively inhibiting its interface reaction with the high-voltage positive electrode, improving the interface stability between the electrolyte and the positive electrode material, while also improving the stability of the electrolyte itself and broadening the electrochemical stability window of the electrolyte, improving the first-efficiency performance and charge and discharge capacity of the battery. In addition, an appropriate amount of oxygen doping not only improves the room temperature ionic conductivity of the sulfide solid electrolyte, but also improves the air stability of the sulfide electrolyte at low dew points, reducing the generation of hydrogen sulfide gas, and at the same time, an appropriate amount of oxygen doping also helps to inhibit the growth of lithium dendrites, mainly because the electrolyte doped with oxygen can form a self-passivating interface SEI layer at the lithium metal interface, thereby improving its compatibility with lithium metal.

[0035] In some embodiments, 0≤x≤1.9, 0.0009≤y≤0.015, 0.20≤z≤0.45. By further limiting the oxygen content of the sulfide solid electrolyte, the electrochemical stability window of the electrolyte can be further broadened, and the compatibility between the electrolyte and the positive electrode material can be improved.

[0036] In some embodiments, 0≤x≤1.7, 0.0018≤y≤0.0144, 0.22≤z≤0.44. For example, when x=1.6, y=0.0009, z=0.22, when x=1.6, y=0.0018, z=0.44, when x=1.6, y=0.0036, z=0.44, when x=1.6, y=0.0072, z=0.44, when x=1.6, y=0.0108, z=0.44, when x=1.6, y=0.0144, z=0.44. By further limiting the oxygen content of the sulfide solid electrolyte, the electrochemical stability window of the solid electrolyte is broadened, and the charge and discharge capacity of the battery is improved.

[0037] In some embodiments, M is at least one of chlorine, bromine, iodine and fluorine. Preferably, M is chlorine.

[0038] In some embodiments, the components of the solid electrolyte include oxygen-doped materials, and the oxygen-doped materials are lithium-containing oxides and / or oxygen-containing lithium salts. Lithium-containing oxides and / or oxygen-containing lithium salts are selected as oxygen-doped materials to avoid the introduction of other metal ions, which may affect the ionic conductivity of the solid electrolyte and the electrochemical stability window of the electrolyte, which may result in poor charge and discharge capacity of the prepared battery. Preferably, the oxygen-doped material is an oxygen-containing lithium salt.

[0039] Specifically, the lithium-containing oxide includes at least one of lithium oxide, lithium peroxide and lithium superoxide, and the oxygen-containing lithium salt includes at least one of lithium carbonate, lithium phosphate, lithium sulfate, lithium acetate and lithium nitrate. Preferably, the lithium-containing oxide is lithium oxide, and the oxygen-containing lithium salt is lithium sulfate. The oxygen-containing lithium salt is selected as lithium sulfate because it has a low cost and can reduce the production cost of the solid electrolyte.

[0040] This embodiment also provides a method for preparing the electrolyte as described in the above embodiment, comprising:

[0041] S1: providing oxygen-doped powder, lithium source, phosphorus source and halide;

[0042] In some embodiments, the lithium source includes at least one of LiH, Li2CO3, LiCl, LiBr, LiI, LiF, Li2S, LiSe and lithium metal. Preferably, the lithium source is Li2S.

[0043] In some embodiments, the phosphorus source includes at least one of P2S5, P4S9, P4S3, and P. Preferably, the phosphorus source is P2S5.

[0044] In some embodiments, the halide comprises at least one of LiCl, LiBr, LiI, I, and LiF. Preferably, the halide is LiCl.

[0045] In some embodiments, providing oxygen-doped powder includes:

[0046] S11: Provide lithium salt and oxygen-doped materials;

[0047] In some embodiments, the lithium salt includes at least one of Li2CO3, Li2S, LiCl, LiOH, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Preferably, the lithium salt is Li2S.

[0048] In some embodiments, the oxygen-doped material is a lithium-containing oxide and / or an oxygen-containing lithium salt. Lithium-containing oxides and / or oxygen-containing lithium salts are selected as oxygen-doped materials to avoid the introduction of other metal ions, which may affect the ionic conductivity of the solid electrolyte and the electrochemical stability window of the electrolyte, which may result in poor charge and discharge capacity of the prepared battery. Preferably, the oxygen-doped material is an oxygen-containing lithium salt.

[0049] Specifically, the lithium-containing oxide includes at least one of lithium oxide, lithium peroxide and lithium superoxide, and the oxygen-containing lithium salt includes at least one of lithium carbonate, lithium phosphate, lithium sulfate, lithium acetate and lithium nitrate. Preferably, the lithium-containing oxide is lithium oxide, and the oxygen-containing lithium salt is lithium sulfate. The oxygen-containing lithium salt is selected as lithium sulfate because it has a low cost and can reduce the production cost of the solid electrolyte.

[0050] S12: Mix the lithium salt and the oxygen-doped material in a certain ratio and grind them to obtain oxygen-doped powder. Grinding can reduce the particle size of the lithium salt and the oxygen-doped material, making them more uniform, which helps to improve the contact and interaction between the two and may form a crystal structure that is more conducive to battery performance.

[0051] In some embodiments, the mass ratio between the oxygen-doped material and the lithium salt is (0.01-0.1):1. By limiting the mass ratio between the oxygen-doped material and the lithium salt, the content of oxygen doping in the electrolyte can be controlled. Excessive oxygen doping in the sulfide solid electrolyte will destroy the crystal structure of the argyrodite-type sulfide, reduce the migration channel of lithium ions, and thus reduce the room temperature ionic conductivity of the electrolyte. Excessive oxygen doping will form a poor interface phase between the electrolyte and the positive electrode, reducing the interface stability between the electrolyte and the electrode material, thereby affecting the overall performance of the battery; and the content of oxygen doped in the sulfide solid electrolyte is small, and it may be difficult to broaden its electrochemical stability window, thereby affecting the charge and discharge performance of the battery and the interface stability between it and the positive electrode material. Preferably, the mass ratio between the oxygen-doped material and the lithium salt is (0.02-0.08):1. Further preferably, the mass ratio between the oxygen-doped material and the lithium salt is 0.04:1.

[0052] In some embodiments, lithium salt and oxygen-doped material are mixed in a certain ratio and then ground to obtain oxygen-doped powder, including: lithium salt and oxygen-doped material are placed in a ball mill in a certain ratio and mixed to obtain mixed powder, and then the ball mill containing the mixed powder is placed in a ball mill for grinding to obtain oxygen-doped powder.

[0053] In some embodiments, the size of the zirconia balls in the grinding process in step S12 is in the range of φ1-φ10. Grinding with zirconia balls of a certain size range makes the oxygen doping distribution more uniform, and makes the powder after grinding have a uniform particle size, which can help improve the ionic conductivity of the electrolyte and the performance of the battery. Preferably, the size of the zirconia balls in the grinding process in step S12 is φ10.

[0054] In some embodiments, the ball-to-material ratio in the grinding process in step S12 is (10-30):1. By limiting the appropriate ball-to-material ratio range, the grinding efficiency is improved, the uniformity of the ground powder is better, and the microstructure of the material is maintained while maintaining the appropriate fineness of the powder, avoiding the problem of excessive refinement of the material grains due to excessive grinding and thus increasing the internal resistance of the electrolyte. Preferably, the ball-to-material ratio in the grinding process in step S12 is (10-20):1. Further preferably, the ball-to-material ratio in the grinding process in step S12 is 15:1.

[0055] In some embodiments, the ball milling speed in the grinding process in step S12 is 50rpm-250rpm. The upper limit of the ball milling speed may be but not limited to 250rpm, 249rpm, 248rpm, etc., and the lower limit of the ball milling speed may be but not limited to 50rpm, 51rpm, 52rpm, etc.; it is understandable that the ball milling speed can also be any point value within the above range, which is not enumerated here. By limiting the appropriate ball milling speed, not only the grinding efficiency is improved, but also the microstructure of the solid electrolyte can be controlled to affect its ionic conductivity, and it is also conducive to achieving more accurate control of the doping amount, thereby improving the chemical stability of the electrolyte. Preferably, the ball milling speed in the grinding process in step S12 is 100rpm-200rpm. Further preferably, the ball milling speed in the grinding process in step S12 is 150rpm.

[0056] In some embodiments, the ball milling time in the milling process in step S12 is 0.5-3h. The upper limit of the ball milling time may be but not limited to 3h, 2.9h, 2.8h, etc., and the lower limit of the ball milling time may be but not limited to 0.5h, 0.6h, 0.7h, etc.; it can be understood that the ball milling time can also be any point value within the above range, which is not enumerated here. By limiting the appropriate ball milling time, the structural integrity of the material is ensured, and the problem of local structural disorder and reduced crystallinity caused by long-term ball milling leading to reduced ionic conductivity of the electrolyte is avoided. Preferably, the ball milling time in the milling process in step S12 is 0.5-1.5h. Further preferably, the ball milling time in the milling process in step S12 is 1.5h.

[0057] In some embodiments, the grinding process in step S12 is performed in an oxygen-free environment. Grinding in an oxygen-free environment avoids oxidation of the material during grinding, which may lead to degradation of the material's performance, such as reduced ion conductivity and poor structural stability, and is also beneficial to improving the efficiency and uniformity of oxygen doping.

[0058] Specifically, the oxygen-free environment during the grinding process is formed by an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, argon, helium, neon and xenon.

[0059] S2: mixing oxygen-doped powder, lithium source, phosphorus source and halide to obtain a precursor material;

[0060] In some embodiments, the mixing process is performed in an oxygen-free environment, where the oxygen-free environment is formed by an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, argon, helium, neon, and xenon.

[0061] In some embodiments, in the precursor material, the molar ratio of the lithium source, the phosphorus source and the halide is (7-x):(6-x):x, wherein 0≤x≤2. Preferably, 0≤x≤1.7. Exemplarily, when x=1.6, the molar ratio of the lithium source, the phosphorus source and the halide is 5.4:4.4:1.6.

[0062] In some embodiments, the mixing time in step S2 is 0.3-1h. The upper limit of the mixing time may be but not limited to 1h, 0.9h, 0.8h, etc., and the lower limit of the mixing time may be but not limited to 0.3h, 0.4h, 0.5h, etc.; it can be understood that the mixing time can also be any point value within the above range, which is not enumerated here. Preferably, the mixing time in step S2 is 0.5-1h. Further preferably, the mixing time in step S2 is 0.5h. S3: Calcine the precursor material in an oxygen-free environment to obtain an oxygen-doped sulfide solid electrolyte.

[0063] In some embodiments, a precursor material is calcined in an oxygen-free environment to obtain an oxygen-doped sulfide solid electrolyte, including: calcining the precursor material in an oxygen-free environment to obtain a calcined oxygen-doped sulfide solid electrolyte, and grinding the calcined oxygen-doped sulfide solid electrolyte to obtain the oxygen-doped sulfide solid electrolyte.

[0064] Specifically, the grinding treatment includes: putting the calcined oxygen-doped sulfide solid electrolyte into a mortar, grinding it, and then sieving it to obtain the oxygen-doped sulfide solid electrolyte.

[0065] In some embodiments, the heating rate during the calcination process in step S3 is 1-5°C / min. The upper limit of the heating rate may be but not limited to 5°C / min, 4.9°C / min, 4.8°C / min, etc., and the lower limit of the heating rate may be but not limited to 1°C / min, 1.1°C / min, 1.2°C / min, etc.; it can be understood that the heating rate can also be any point value within the above range, which is not enumerated here. A suitable heating rate can promote the uniform growth of grains in the material, help to form a denser microstructure, and thus improve the ionic conductivity of the electrolyte and optimize the electrochemical performance of the battery. Preferably, the heating rate during the calcination process in step S3 is 1-2°C / min. Further preferably, the heating rate during the calcination process in step S3 is 1°C / min.

[0066] In some embodiments, the calcination temperature in the calcination process in step S3 is 400-550°C. The upper limit of the calcination temperature may be but not limited to 550°C, 549°C, 548°C, etc., and the lower limit of the calcination temperature may be but not limited to 400°C, 401°C, 402°C, etc.; it can be understood that the calcination temperature can also be any point value within the above range, which is not enumerated here. A suitable calcination temperature can promote the uniform growth of grains, while helping the material to form fewer grain boundaries and smoother crystal planes, thereby improving the ionic conductivity and chemical stability of the electrolyte. Preferably, the calcination temperature in the calcination process in step S3 is 470-550°C. Further preferably, the calcination temperature in the calcination process in step S3 is 480°C.

[0067] In some embodiments, the calcination time in the calcination process in step S3 is 6-20h. The upper limit of the calcination time may be but not limited to 20h, 19h, 18h, etc., and the lower limit of the calcination time may be but not limited to 6h, 7h, 8h, etc.; it is understandable that the calcination time can also be any point value within the above range, which is not enumerated here. Appropriate calcination time can promote the uniform growth of grains, avoid excessive growth leading to degradation of electrolyte performance, and also avoid the calcination time being too long, resulting in defects and impurities that lead to reduced ionic conductivity and chemical stability of the electrolyte. Preferably, the calcination time in the calcination process in step S3 is 8-16h. Further preferably, the calcination time in the calcination process in step S3 is 12h.

[0068] In some embodiments, the oxygen-free environment during the calcination process is formed by an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, argon, helium, neon, and xenon.

[0069] The preparation method of the above-mentioned electrolyte adopted in the present application adopts a two-step mixing method, which can fully improve the uniformity and dispersibility of the material. At the same time, the oxygen doping process provided in the present application adopts a highly repeatable ball milling process, which is simple to operate and has high repeatability. The selected doping raw materials are low in price and easy to mass produce.

[0070] In some embodiments, the oxygen-doped sulfide solid electrolyte has a chemical formula of Li 7-x+2y+2z PS 6-x+y+z M x O 4y, wherein M is a halogen element, 0≤x≤2, 0≤y≤0.02, 0.1≤z≤0.5. Preferably, 0≤x≤1.9, 0.0009≤y≤0.015, 0.20≤z≤0.45. More preferably, 0≤x≤1.7, 0.0018≤y≤0.0144, 0.22≤z≤0.44. For example, when x=1.6, y=0.0009, z=0.22, when x=1.6, y=0.0018, z=0.44, when x=1.6, y=0.0036, z=0.44, when x=1.6, y=0.0072, z=0.44, when x=1.6, y=0.0108, z=0.44, when x=1.6, y=0.0144, z=0.44.

[0071] In some embodiments, M is at least one of chlorine, bromine, iodine and fluorine. Preferably, M is chlorine.

[0072] The specific embodiments of the present application are introduced below in combination with the above-mentioned oxygen-doped sulfide solid electrolyte and its preparation method. The following embodiments describe the technical solution of the present application in more detail, and these embodiments are only used for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the embodiments can be obtained by commercial purchase or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained commercially.

[0073] Example 1

[0074] The present embodiment provides a method for preparing an oxygen-doped sulfide solid electrolyte, which specifically includes the following steps: S1: Under the protection of an inert atmosphere, 20 g of lithium sulfide and 0.2 g of lithium sulfate are respectively added to a ball mill to mix to obtain a mixed powder, the ball mill containing the mixed powder is taken out of the glove box, zirconium oxide balls are added to the ball mill containing the mixed powder, and the ball mill is placed in a ball mill for grinding to obtain oxygen-doped powder, wherein the size of the zirconium oxide balls in the grinding process is φ10, the ball-to-material ratio is 10:1, the ball mill speed is 100 rpm, the ball mill time is 0.5 h, and the mass ratio between lithium sulfate and lithium sulfide is 0.01:1.

[0075] S2: Under the protection of an inert atmosphere, oxygen-doped powder, 3.2860 g Li2S (purity: 99.9%), 4.2209 g P2S5 (purity: 99.9%) and 2.5630 g LiCl (purity: 99.5%) were placed in a mortar and mixed for 0.5 h to obtain a precursor material.

[0076] S3: The precursor material is placed in a muffle furnace filled with an inert atmosphere for calcination, heated to 480°C at a heating rate of 2°C / min, and then calcined for 8 hours, and then cooled to room temperature with the furnace to obtain the calcined oxygen-doped sulfide solid electrolyte. The calcined oxygen-doped sulfide solid electrolyte is taken out of the muffle furnace, ground in a mortar and passed through a 60-mesh sieve to obtain the oxygen-doped sulfide solid electrolyte. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x+2y+ 2z PS 6-x+y+z M x O 4y , where x=1.6, y=0.0018, z=0.44.

[0077] Example 2

[0078] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the ball-to-material ratio in step S1 is 15:1.

[0079] Example 3

[0080] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the same points as those in Embodiment 2 are not repeated here. The difference between this embodiment and Embodiment 2 is that the ball milling speed in step S1 is 150 rpm.

[0081] Example 4

[0082] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the same points as those in Embodiment 2 are not repeated here. The difference between this embodiment and Embodiment 2 is that the ball milling speed in step S1 is 200 rpm.

[0083] Example 5

[0084] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the same points as those in Embodiment 3 are not repeated here. The difference between this embodiment and Embodiment 3 is that the ball milling time in step S1 is 1 hour.

[0085] Example 6

[0086] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the same points as those in Embodiment 5 are not repeated here. The difference between this embodiment and Embodiment 5 is that the ball milling time in step S1 is 1.5 h.

[0087] Example 7

[0088] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Example 6 are not repeated here. The difference between this method and Example 6 is as follows: S1: Under the protection of an inert atmosphere, 20 g of lithium sulfide and 0.4 g of lithium sulfate are added to a ball mill respectively and mixed to obtain a mixed powder. The mass ratio of lithium sulfate to lithium sulfide is 0.02:1. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x+2y+2z PS 6-x+y+z M x O 4y , where x=1.6, y=0.0036, z=0.44.

[0089] Example 8

[0090] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Example 7 are not repeated here. The difference between this method and Example 7 is as follows: S1: Under the protection of an inert atmosphere, 20 g of lithium sulfide and 0.8 g of lithium sulfate are added to a ball mill respectively and mixed to obtain a mixed powder. The mass ratio of lithium sulfate to lithium sulfide is 0.04:1. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x+2y+2z PS 6-x+y+z M x O 4y , where x=1.6, y=0.0072, z=0.44.

[0091] Example 9

[0092] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Example 8 are not repeated here. The difference between this embodiment and Example 8 is as follows: S1: Under the protection of an inert atmosphere, 20 g of lithium sulfide and 1.2 g of lithium sulfate are added to a ball mill respectively and mixed to obtain a mixed powder. The mass ratio of lithium sulfate to lithium sulfide is 0.06:1. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x+2y+2z PS 6-x+y+z M x O 4y , where x=1.6, y=0.0108, z=0.44.

[0093] Example 10

[0094] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Embodiment 9 are not repeated here. The difference between this embodiment and Embodiment 9 is as follows: S1: Under the protection of an inert atmosphere, 20 g of lithium sulfide and 1.6 g of lithium sulfate are added to a ball mill respectively and mixed to obtain a mixed powder. The mass ratio of lithium sulfate to lithium sulfide is 0.08:1. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x+2y+2zPS 6-x+y+z M x O 4y , where x=1.6, y=0.0144, z=0.44.

[0095] Embodiment 11

[0096] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Example 8 are not repeated here. The difference between this embodiment and Example 8 is that the heating rate during the calcination process in step S3 is 1° C. / min.

[0097] Example 12

[0098] This embodiment provides a method for preparing an oxygen-doped solid electrolyte, and the similarities with Example 11 are not repeated here. The difference between this embodiment and Example 11 is that the calcination time in the calcination process in step S3 is 12 hours.

[0099] Embodiment 13

[0100] This embodiment provides a method for preparing an oxygen-doped solid electrolyte. The same points as those in Example 12 are not repeated here. The difference between this embodiment and Example 12 is that the calcination time in the calcination process in step S3 is 16 hours.

[0101] Comparative Example 1

[0102] This comparative example provides a method for preparing an oxygen-doped sulfide solid electrolyte, which specifically comprises the following steps: S1: Under the protection of an inert atmosphere, 3.2860 g of Li2S (purity of 99.9%), 4.2209 g of P2S5 (purity of 99.9%) and 2.5630 g of LiCl (purity of 99.5%) are put into a mortar and mixed for 0.5 h to obtain a precursor material.

[0103] S2: The precursor material is placed in a muffle furnace filled with an inert atmosphere for calcination, heated to 480°C at a heating rate of 1°C / min, and then calcined for 16 hours, and then cooled to room temperature with the furnace to obtain a calcined oxygen-doped sulfide solid electrolyte. The calcined oxygen-doped sulfide solid electrolyte is taken out of the muffle furnace, ground in a mortar and passed through a 60-mesh sieve to obtain an oxygen-doped sulfide solid electrolyte. The chemical formula of the obtained oxygen-doped sulfide solid electrolyte is Li 7-x PS 6-x M x , where x=1.6.

[0104] The above examples and comparative examples adopt the following testing methods:

[0105] 1. The relevant X-ray diffraction data of the oxygen-doped sulfide solid electrolyte obtained in Example 12 were measured using an X-ray diffractometer. The setting conditions were: acceleration voltage 40 KV, Cu target, scanning speed: 10° / min, step length: 0.02°, diffraction angle: 10°-80°. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the XRD spectrum peak position and peak intensity are completely consistent with the Li7PS6 standard card, indicating that the synthesized material is a pure phase substance without impurities.

[0106] 2. The sulfide solid electrolytes prepared in the examples and comparative examples were tested for ionic conductivity at 25°C using an electrochemical workstation, wherein the ionic conductivity test was performed according to the conductivity calculation formula: (L is the thickness of the sample, R is the total impedance, and S is the effective area of ​​contact between the sample and the electrode) The total ionic conductivity was calculated and the test results are shown in Table 1 below.

[0107] 3. The solid electrolytes prepared in Example 12 and Comparative Example 1 were used to prepare a principle battery for charge and discharge evaluation.

[0108] (1) The assembly process of the principle battery is as follows: the positive electrode of the principle battery uses the positive electrode active material HN586, the solid electrolyte is the oxygen-doped sulfide solid electrolyte obtained in the above-mentioned comparative example 1 and example 12, and the negative electrode active material is a silicon film. The positive electrode powder is prepared by hand-grinding and mixing the positive electrode active material HN856, the oxygen-doped sulfide solid electrolyte and the conductive additive (VGCF) in a ratio of 7:2.5:0.5, and then filling 150 mg of the sulfide solid electrolyte into the insulating cylinder of the sealed battery, uniaxially forming at 120 MPa, filling 38.5 mg of positive electrode powder and the negative electrode silicon film on both sides of the prepared electrolyte layer respectively, and then forming together with the solid electrolyte layer at 350 MPa, and then tightening with a pressure screw with a torque of 10 N·m to make a principle battery.

[0109] (2) The electrochemical performance of the principle battery was tested using a Xinwei (CT4080-5V10mA) battery tester with a test voltage range of 2.0 to 4.3 V and a test current of 0.2 mA. The test results are shown in Table 2 below.

[0110] (3) Combination Figure 2It can be seen from Table 2 that the principle battery prepared by the electrolyte doped with 4% Li2SO4 in Example 12 has a charging capacity of 240.01mAh / g at 0.05C, a discharge capacity of 195.34mAh / g, and a first efficiency of 81.39%, which are significantly higher than the relevant performance of the principle battery prepared in Comparative Example 1 (the charging capacity at 0.05C is 225.596mAh / g, the discharge capacity is 170.75mAh / g, and the first efficiency is 75.57%). It can be seen that by introducing an appropriate amount of oxygen into the solid electrolyte, oxygen replaces part of the sulfur in the electrolyte and optimizes the components of the electrolyte, the room temperature ionic conductivity of the sulfide electrolyte is greatly improved, the stability of the electrolyte itself and its interface stability with the positive electrode material are also improved, and the charge and discharge capacity and first efficiency of the principle battery are improved.

[0111] The following table 1 statistically records the test data in the embodiments and comparative examples:

[0112] Table 1

[0113]

[0114] Table 2

[0115]

[0116] With reference to Table 1, Table 2 and the accompanying drawings, in combination with Example 1 and Example 2, it can be seen that, with other conditions remaining unchanged, increasing the ball-to-material ratio during the grinding process slightly improves the room temperature ionic conductivity of the material. This may be because increasing the ball-to-material ratio leads to better material uniformity, which helps to form more ion transport channels and reduce the energy barrier for ion migration.

[0117] Combining Example 3 and Example 4, it can be seen that when other conditions remain unchanged, increasing the ball mill speed during the grinding process actually reduces the room temperature ionic conductivity of the electrolyte. This may be because the increase in the ball mill speed may cause excessive fragmentation of the material, destroying the microstructure that is conducive to ion transport, thereby causing the ionic conductivity of the material to decrease.

[0118] In combination with Example 3, Example 5 and Example 6, it can be seen that, with other conditions remaining unchanged, increasing the grinding time during the grinding process can improve the room temperature ionic conductivity of the electrolyte to a certain extent. Appropriate ball milling time ensures the structural integrity of the material and avoids the problem of local structural disorder and reduced crystallinity caused by long-term ball milling, which leads to a decrease in the ionic conductivity of the electrolyte.

[0119] In combination with Examples 6-10, it can be seen that, with other conditions remaining unchanged, the amount of lithium sulfate added is regulated so that an appropriate amount of oxygen is doped into the electrolyte to avoid excessive oxygen doping in the sulfide solid electrolyte, which will destroy the crystal structure of the argyrodite-type sulfide, reduce the migration channel of lithium ions and thus reduce the room temperature ionic conductivity of the material. At the same time, a low content of doped oxygen will also make it difficult to broaden the chemical stability window of the electrolyte and will also reduce the ionic conductivity of the material.

[0120] In combination with Examples 11-13, it can be seen that, with other conditions unchanged, regulating the calcination time will affect the ionic conductivity of the electrolyte. When the calcination time is too short, the material fails to fully react or the grain growth is insufficient, resulting in reduced ionic conductivity. When the calcination time is too long, the grains will grow excessively and the number of grain boundaries will increase. Excessive grain boundaries will hinder the long-distance migration of ions and thus reduce ionic conductivity.

[0121] Combining Example 12 and Comparative Example 1, it can be seen that, when other conditions remain unchanged, after doping an appropriate amount of oxygen in the solid electrolyte, the charge and discharge capacity and first efficiency of the obtained battery are greatly enhanced, and the room temperature ionic conductivity of the material is also increased to 11.5 mS / cm. This may be due to the replacement of part of the sulfur in the electrolyte by oxygen, which broadens the electrochemical window of the electrolyte, thereby improving its stability with the positive electrode material, and at the same time greatly improves the room temperature ionic conductivity of the sulfide electrolyte, thereby improving the charge and discharge capacity and first efficiency of the battery.

[0122] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. An oxygen-doped sulfide solid electrolyte, characterized in that: The solid electrolyte has the general chemical formula of Li 7-x+2y+2z PS 6-x+y+z M x O 4y , wherein M is a halogen element, 0≤x≤2, 0≤y≤0.02, 0.1≤z≤0.

5.

2. The electrolyte according to claim 1, characterized in that 0≤x≤1.9, 0.0009≤y≤0.015, 0.20≤z≤0.

45.

3. The electrolyte according to claim 1, characterized in that 0≤x≤1.7, 0.0018≤y≤0.0144, 0.22≤z≤0.

44.

4. The electrolyte according to any one of claims 1 to 3, characterized in that The components of the solid electrolyte include oxygen-doped materials, and the oxygen-doped materials are lithium-containing oxides and / or oxygen-containing lithium salts.

5. A method for preparing an electrolyte according to any one of claims 1 to 4, characterized in that: include: S1: providing oxygen-doped powder, lithium source, phosphorus source and halide; S2: mixing the oxygen-doped powder, the lithium source, the phosphorus source and the halide to obtain a precursor material; S3: calcining the precursor material in an oxygen-free environment to obtain the oxygen-doped sulfide solid electrolyte.

6. The preparation method according to claim 5, characterized in that: Oxygen doped powders include: S11: Provide lithium salt and oxygen-doped materials; S12: mixing the lithium salt and the oxygen-doped material in a certain ratio and grinding them to obtain the oxygen-doped powder.

7. The preparation method according to claim 6, characterized in that: The mass ratio between the oxygen-doped material and the lithium salt is (0.01-0.1):

1.

8. The preparation method according to claim 6, characterized in that: The method satisfies at least one of the following characteristics: The size range of the zirconia balls during the grinding process in step S12 is φ1-φ10; The ball-to-material ratio in the grinding process in step S12 is (10-30):1; The ball milling speed in the grinding process in step S12 is 50 rpm-250 rpm; The ball milling time in the grinding process in step S12 is 0.5-3h; The grinding process in step S12 is performed in an oxygen-free environment.

9. The preparation method according to claim 5, characterized in that: The method satisfies at least one of the following characteristics: The heating rate during the calcination process in step S3 is 1-5°C / min; The calcination temperature in the calcination process in step S3 is 400-550°C; The calcination time in the calcination process in step S3 is 6-20 hours.

10. The preparation method according to claim 5, characterized in that: The oxygen-doped material is a lithium-containing oxide and / or an oxygen-containing lithium salt.

Citation Information

Cited By

  • Argyrodite type sulfide solid electrolyte and preparation method and application thereof

    CN121609307A